Optimized Temporary Frequency Support for Wind Power Plants Considering Expanded Operational Region of Wind Turbines - Zhengyang Hu; Bingtuan Gao; Zhao Xu; Sufan Jiang (CSEE Journal of Power and Energy Systems, 2025)
Wind power plants (WPPs) are increasingly mandated to provide temporary frequency support to power systems during contingencies involving significant power shortages. However, the frequency support capabilities of WPPs under derated operations remain insufficiently investigated, highlighting the potential for further improvement of the frequency nadir. This paper proposes a bi-level optimized temporary frequency support (OTFS) strategy for a WPP. The implementation of the OTFS strategy is collaboratively accomplished by individual wind turbine (WT) controllers and the central WPP controller. First, to exploit the frequency support capability of WTs, the stable operational region of WTs is expanded by developing a novel dynamic power control approach in WT controllers. This approach synergizes the WTs' temporary frequency support with the secondary frequency control of synchronous generators, enabling WTs to release more kinetic energy without causing a secondary frequency drop. Second, a model predictive control strategy is developed for the WPP controller. This strategy ensures that multiple WTs operating within the expanded stable region are coordinated to minimize the magnitude of the frequency drop through efficient kinetic energy utilization. Finally, comprehensive case studies are conducted on a real-time simulation platform to validate the effectiveness of the proposed strategy.